Correction of reproductive behavior malfunctions of male rats with experimental hypogonadism affected by cadmium chloride intoxication by means of hormonotherapy and transplantation of interstitial cells suspension - Пахомов, О. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
Changes in reproductive behavior of animals after transplantation of interstitial cell suspension (ICS) and hormonotherapy with chorionic gonadotropine (hCG) have been studied using model of experimental toxic hypogonadism, affected by injection of cadmium chloride (CC). It has been shown that ISC combined with exogenous hCG can promote increase in reproductive activity reparing after gonadotoxic factors impact. It can be evidenced mostly through the activation of proceptory behavior as well as through the increase in the components of reproductive process – mountings, intromissions and ejaculations. Combined use of ICS transplantations and hormone therapy makes it possible to reduce significantly the dosage of exogenous hCG to compensate states resulting from the toxic injury of gonads.